Apomixis and Hybridization Drives Reticulate Evolution and Phyletic Differentiation in Sorbus L.: Implications for Conservation - Hamston, Tracey J.; de Vere, Natasha; King, R. Andrew; Pellicer, Jaume; Fay, Michael F.; Cresswell, James E.; Stevens, Jamie R. (Frontiers in Plant Science, 2018)
Hybridisation and polyploidy are major forces in the evolution of plant diversity and the study of these processes are of particular interest to understand how novel taxa are formed and maintain genetic integrity. Sorbus is an example of a genus where active diversification and speciation are ongoing and, as such, represents an ideal model to investigate the roles of hybridisation, polyploidy and apomixis in a reticulate evolutionary process. To elucidate breeding systems and evolutionary origins of a complex of closely related Sorbus taxa, we assessed genotypic diversity and population structure within and among taxa, combining data from nuclear DNA microsatellite markers and flow cytometry. Clonal analysis and low genotypic diversity within the polyploid taxa suggest apomixis is obligate. However, genetic variation has led to groups of ‘clone-mates’ within apomictic taxa that strongly suggest mutation is responsible for the genotypic diversity of these apomictic lineages. In addition, microsatellite profiles and site demographics suggest hybridisation events among apomictic polyploid Sorbus may have contributed to the extant diversity of recognised taxa in this region. This research demonstrates that both macro- and micro-evolutionary processes are active within this reticulate Sorbus complex. Conservation measures should be aimed at maintaining this process and should therefore be prioritised for those areas of Sorbus species richness where potential for interspecific gene flow is greatest.